Évaluer la créativité à travers le degré de solidité de ses évaluations. Une approche relationnelle - Thomas Martine; François Cooren (Communiquer)
Arguably, one of the main obstacles to creativity assessment is that creativity criteria are likely to change depending on what is assessed and who is making the assessment. In this paper, we argue that we can solve this problem by adopting a relational ontology, i.e., an ontology according to which beings of the world acquire their properties by relating to other beings. First, we present the main consequences of this ontological approach for creativity assessment: (1) Accounting for the creativity of a given object (e.g., a person, a product or a process) involves retracing the beings (including criteria) that relate it to its alleged creativity. (2) One can assess the creativity of this object by looking at the number of beings that substantiate this relation, i.e., by looking at what we propose to call the “degree of solidity” of the relation. (3) One can thus account for the specificity of various forms of creativity (including their specific criteria) and, at the same time, compare them in terms of solidity. Building on these ontological assumptions, we then present a new assessment technique, the Objection Counting Technique (OCT), before putting it to the test using an excerpt taken from a naturally-occurring brainstorming session.